Effect of Tungsten Carbides on Abrasive Wear of Hardfacing Coatings. (4th June 2018) - Pichler, Philip; Leitner, Martin; Grün, Florian; Haßler, Jürgen
Abstract : The aim of this study is to investigate the abrasive wear loss as well as the wear mechanisms of hardfacing layers with and without tungsten carbides (WC) included in the matrix in different friction wheel test (FWT) configurations. The FWT setup is varied in regard to the materials of the rotating wheels, whereat steel and rubber materials are utilized to achieve varying wear mechanisms as representative conditions for stone milling as well as low density wood cutting processes. Coatings including fine particles of WC highlight the highest resistance against abrasive wear in rubber wheel testing condition, at which microcutting acts as the dominant effect. In comparison to the hardfacings without WC, the mean material loss majorly decreases by about 75%. On the contrary, the mean material loss of fine WC reinforced coatings increases up to 93% compared to the condition without WC if a steel wheel is utilized as rotating counterpart. Thereby, the coatings with comparably coarse WC reveal the minimum material loss with a decrease over 70% compared to the condition without WC. In conclusion, the inclusion of WC in hardfacing coatings significantly increases the wear resistance. The experimental wear test results highlight the fact that in order to achieve the optimal wear resistance the material characteristics of the hardfacings need to be properly defined considering the predominant wear mechanisms under in-service conditions.